The approach to elbow pain in the pediatric and adolescent throwing athlete - Hammoud, S.; Sgromolo, N.; Atanda, A. (The Physician and Sportsmedicine, 2014)
Elbow pain in pediatric throwing athletes can be very concerning and challenging to diagnose. Diagnosis involves determining whether the injury is chronic or acute in nature and the anatomical location of the pain. Physicians should be aware of the sport-specific forces that predispose athletes with immature skeletons to injury and should be familiar with the common presentations of these injuries. In order to narrow the diagnosis, physicians should gather a detailed history of how and when the pain occurred in addition to performing a thorough physical exam that includes tests, such as the modified milking maneuver and the moving valgus stress test. Appropriate imaging helps physicians to confirm the diagnosis and elucidates any associated pathology in patients. In most cases, the treatment given to patients is conservative and involves rest, ice, non-steroidal anti-inflammatory drugs for pain, and an appropriate physical therapy regimen with a progressive return to play when symptoms have resolved. When patients fail to respond to conservative treatment, surgical intervention may be needed. Knowing when to refer patients for orthopedic evaluation helps athletes return to play quickly and safely.